Oncoplastic Breast Reduction Technique and Outcomes: An Evolution over 20 Years. Issue 4 (April 2017) - Losken, Albert; Hart, Alexandra M.; Broecker, Justine S.; Styblo, Toncred M.; Carlson, Grant W.
Abstract : Background: Reduction mammaplasty at the time of lumpectomy is a good option in women with breast cancer and macromastia. We critically evaluated refinements and outcomes of this technique. Methods: A prospectively maintained database was reviewed of all women with breast cancer who received lumpectomy and reduction mammaplasty at our institution from 1994 to 2015. Patients' demographics were reviewed. Preoperative and postoperative patient satisfaction (BREAST-Q) was determined. Comparisons were made between early and recent cases. Results: There were 353 patients included. Average age was 54 (range, 21 to 80 years), with the largest number having stage I disease [ n = 107 of 246 (43.5 percent)]. Average lumpectomy specimen was 207 g (range, 11.6 to 1954 g) and total reduction weight averaged 545 g (range, 21 to 4102 g). Tumor size averaged 2.02 cm (range, 0.00 to 15.60 cm). The positive margin rate was 6.2 percent ( n = 22). Completion mastectomy rate was 9.9 percent ( n = 35). Overall complication rate was 16 percent. The recurrence rate was 5.2 percent ( n = 10 of 192) at a mean follow-up of 2 years (range, 2 months to 15 years). Resection weights greater than 1000 g were associated with having a positive margin (16.7 percent versus 5.0 percent; p = 0.016), and tended to be associated with having a completion mastectomy ( p = 0.069). Positive margin and completion mastectomy rates have been lower in the past 10 years. Over 1 year postoperatively, women reported increased self-confidence ( p = 0.020), feelings of attractiveness ( p = 0.085), emotional health ( p = 0.037), and satisfaction with sex life ( p = 0.092). Conclusions: The oncoplastic reduction technique is effective and results in improved patient-reported outcomes. Resections over 1000 g are associated with a higher incidence of positive margins and may increase the risk for completion mastectomy. Outcomes have improved with experience and refinement in technique. Abstract : This and Related "Classic" Articles Appear on Prsjournal.Com for Journal Club Discussions.